Normal presenting levels of high-sensitivity troponin and myocardial infarction. Issue 21 (19th April 2013) - Hoeller, Rebeca; Rubini Giménez, María; Reichlin, Tobias; Twerenbold, Raphael; Zellweger, Christa; Moehring, Berit; Wildi, Karin; Freese, Michael; Stelzig, Claudia; Hartmann, Beate; Stoll, Melanie; Mosimann, Tamina; et al.
Abstract : Objective: To analyse whether levels of high-sensitivity cardiac troponin (hs-cTn) below their respective 99th percentile can be used as a single parameter to rule out acute myocardial infarction (AMI) at presentation. Design: Prospective, multicentre study. Main outcome measures: We measured hs-cTn using four different methods (hs-cTnT Roche, hs-cTnI Siemens, hs-cTnI Beckman Coulter and hs-cTnI Abbott) in consecutive patients presenting to the emergency department with acute chest pain. Two independent cardiologists adjudicated the final diagnosis. Patients were followed for death or AMI during a mean period of 24 months. Results: Among 2072 consecutive patients with hs-cTnT measurements available, 21.4% had an adjudicated diagnosis of AMI (sensitivity 89.6%, 95% CI 86.4% to 92.3%, negative predictive value (NPV): 96.5%, 95% CI 95.4% to 97.4%). Among 1180 consecutive patients with hs-cTnI Siemens measurements available, 20.0% had AMI (sensitivity 94.1%, 95% CI 90.3% to 96.7%, NPV: 98.0%, 95% CI: 96.6% to 98.9%). Among 1151 consecutive patients with hs-cTnI Beckman Coulter measurements available, 19.7% had AMI (sensitivity 92.1%, 95% CI 87.8% to 95.2%, NPV: 97.5%, 95% CI 96.0% to 98.5%). Among 1567 consecutive patients with hs-cTnI Abbott measurements available, 20.0% had AMI (sensitivity 77.2%, 95% CI 72.1% to 81.7%, NPV: 94.3%, 95% CI 92.8% to 95.5%). Conclusions: Normal hs-cTn levels at presentation should not be used as a single parameter to rule out AMI as 6%–23% of adjudicated AMI cases had normal levels of hs-cTn levels at presentation. Our data highlight the lack of standardisation among hs-cTnI assays resulting in substantial differences in sensitivity and NPV at the 99th percentile.